Rapid expansion of meso-megathermal rain forests into the southern high latitudes at the onset of the Paleocene-Eocene Thermal Maximum - Huurdeman, Emiel; Frieling, J.; Reichgelt, T.; Bijl, P. K.; Bohaty, S. M.; Holdgate, G. R.; Gallagher, S. J.; Peterse, F.; Greenwood, D. R.; Pross, Jörg (Geology, 2020)
Current knowledge of terrestrial ecosystem response to the Paleocene-Eocene Thermal Maximum (PETM; ca. 56 Ma) is largely based on the midlatitudes of the Northern Hemisphere. To more fully reconstruct global terrestrial ecosystem response to the PETM, we generated vegetation and biomarker proxy records from an outcrop section on the southern coast of Australia (∼60°S paleolatitude). We documented a rapid, massive, and sustained vegetation turnover as a response to regional PETM warming of ∼1-4 °C, abruptly transitioning from a warm temperate to a meso-megathermal rain forest similar to that of present-day northeastern Queensland, Australia. The onset of this vegetation change preceded the characteristic PETM carbon-isotope excursion (CIE) by several thousand years. The reconstructed ecosystem change is much stronger than in other Southern Hemisphere records, highlighting the need for consideration of regional paleoceanographic, paleogeographic, and biogeographic characteristics to fully understand the global terrestrial ecosystem response to PETM climate forcing.
Gesehen am 11.02.2021